The Effects of Anxiety and Depression in Outcomes of Patients with Total Ankle Replacement. Issue 4 (November 2022) - Nam, Hannah; Martinazzi, Brandon J.; Kirchner, Gregory; Bonaddio, Vincenzo; Koroneos, Zachary; Manto, Kristen; Ptasinski, Anna; Aynardi, Michael C.
Category: Ankle Arthritis; Ankle; Other Introduction/Purpose: Pain control is important following TAA. Prior studies have reported that anxiety and depression are associated with worse outcomes after orthopaedic surgery. However, the association between anxiety and depression on patient reported outcomes following TAA is not well-defined. Therefore, the purpose of this study was to investigate the effects of anxiety and depression on postoperative reported pain control following TAA. Methods: Following institutional review board approval, a retrospective chart review was conducted for all patients that underwent TAA from 2018-2021 at our institution. Patients were separated into two groups. Group A consisted of patients with a documented pre-operative history of anxiety and depression and Group B consisted of patients without documented anxiety or depression. Electronic records were reviewed at 2- and 6-weeks following surgery. Statistical analysis was then run to determine the relative risk of poorly controlled pain postoperatively in patients with and anxiety and depression. Results: At our institution, from 2018-2021, 56 patients underwent TAA. The mean age of our cohort was 60.9 (Range, 56-83). In our cohort, 31 patients were male, 25 were female, the mean patient BMI was 33.8 (Range, 21-56.2), 8 patients reported poor pain control (14.3%) and 24 patients had anxiety or depression (42.9%). Of the patients with anxiety or depression, 4 reported poor pain control. There was no statistically significant increased risk of poor pain control in patients with a history of anxiety or depression (RR: 1.5; 95% CI: 0.4145 to 5.4279). Conclusion: Despite the increased risk of poor outcomes reported in patients with a history of anxiety and depression, the results from our cohort indicate that a history of anxiety or depression is not associated with going on to have poor pain control following TAA. Albeit, our sample size was small, warranting further investigation.